BANK RUN AND STABILITY OF ISLAMIC BANKING IN INDONESIA - Kasri, Rahmatina A.; Arundina, Tika; Indraswari, Kenny D.; Prasetyo, M. Budi (Bank Indonesia, 2017)
Bank run is an important economic phenomenon which increasingly occurred in in modern banking system and potentially threatened banking stability as it could trigger a banking crisis. However, most studies related to bank run focus on the occurrence of bank run in conventional banking system. Very few of them discuss the bank run phenomenon under Islamic banking system or dual banking system where Islamic banks jointly operating with conventional banks. Therefore, this study attempts to analyze the determinants of bank run in the Indonesian Islamic banking industry by employing primary data from 256 customers of Indonesia Islamic banks in 2015 and by utilizing factor analysis and descriptive statistics. In theory, Islamic banks tend to be more resilient towards any macroeconomic or financial shocks as compared to conventional banks due to the nature of its asset-based and risk-sharing arrangement. However, the result exhibits that both psychological and fundamental factors (i.e. macroeconomics and bank fundamentals) strongly influence the behaviors of Islamic banking depositors to withdraw their funds, which might trigger the occurrence of bank runs in the country. Insider information, macroeconomic condition and bank fundamental factors are also shown to have the highest impacts among all variables. Hence, in the context of banking stability, the finding implies that Islamic banks are not completely immune to the impacts of macroeconomic shocks or financial crisis. As a country with a dual banking system, Indonesia had experienced several bank runs since 1990s. Therefore, the findings of the study should provide the policy makers important insight into research based-policy in order to attain financial stability as one of the main economic goals of the country.